Catalyst for preparing acrylonitrile through propylene ammoxidation as well as preparation method and application of catalyst

By using Fe, Mo, Bi composite oxides and silica support in the acrylonitrile catalyst, the peak temperature and peak strength of the catalyst are optimized, and the problems of low acrylonitrile yield and poor stability of the catalyst under high load conditions are solved, and the problem of low acrylonitrile yield and poor stability of the catalyst is achieved. Efficient production of acrylonitrile.

CN119215916AActive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310782814.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The existing acrylonitrile catalyst has low yield and poor stability under high load conditions, which cannot meet the needs of industrial production.

Method used

Complex oxides are used as active components, including oxides of three elements: Fe, Mo and Bi. The atomic molar ratio of Bi/Mo is 0.005-0.30, the atomic molar ratio of Fe/Mo is 0.02-1.0, and dioxide is oxidized. Silicon is the support, and the peak temperature and peak strength of the catalyst is optimized through program temperature-raising reduction experiments to form a catalyst with high propylene ammonia oxidation activity and selectivity.

Benefits of technology

Maintaining high acrylonitrile single-pass yield for a long time under high load conditions improves the efficiency and economy of acrylonitrile production. The propylene conversion rate of the catalyst can reach more than 99%, and the acrylonitrile single-pass yield can reach more than 84%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215916A_ABST
    Figure CN119215916A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing acrylonitrile through propylene ammoxidation as well as a preparation method and application of the catalyst. The catalyst comprises an active component and a carrier, and when the catalyst is subjected to a temperature programmed reduction experiment in a flowing Ar atmosphere containing 5% of H2 at a heating rate of 10 DEG C / min, the peak intensity ratio of a first reduction peak at the peak temperature of 400-600 DEG C to a second reduction peak at the peak temperature of 600-800 DEG C is (2.5: 1)-(1.5: 1). When the catalyst is used for preparing acrylonitrile through propylene ammoxidation, the catalyst has relatively high propylene ammoxidation activity and acrylonitrile selectivity, meanwhile, the catalyst has relatively long service life under a high-load condition, and relatively high acrylonitrile single-pass yield can be maintained for a long time, so that the efficiency and economical efficiency of acrylonitrile production are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalyst for preparing acrylonitrile by oxidation of propylene ammonia, a preparation method and an application thereof. Background Art

[0002] Acrylonitrile is an important basic chemical raw material, and is currently produced by fluidized bed ammoxidation process. Catalysts are one of the core technologies of this process, and research and improvement on them have never stopped. Currently, Mo-Bi catalysts have been widely used in industry.

[0003] Increasing the catalyst load (WWH), i.e., the tons of propylene that can be processed per ton of catalyst per hour, can reduce the catalyst loading in the reactor under the same production capacity, which is of great significance for reducing the design size of large-scale devices and expanding the capacity of existing devices, and is an important trend in the development of acrylonitrile catalysts at present. However, with the increase of catalyst load, the feed amount of the reactor increases, the contact time of the corresponding catalyst with the raw material will also be shortened, and higher requirements are also put forward for the redox performance of the catalyst itself. The existing catalysts cannot fully adapt to the requirements under high-load conditions due to their own redox performance, and are very likely to produce a rapid decrease in acrylonitrile yield and poor stability when used under high-load conditions.

[0004] CN111744493A discloses an acrylonitrile catalyst, which can improve the stability of the catalyst during long-term operation by controlling the relative size of the Mo / Bi element molar ratio on the surface of the catalyst particles and the Mo / Bi element molar ratio in the bulk phase, but the load used in the catalyst evaluation is relatively low.

[0005] CN107282063B, CN107282060B, CN107282065B and CN107282094B disclose that adding a certain amount of zirconium oxide, titanium oxide, diatomaceous earth and ZSM-5 molecular sieve as carrier modifiers during the catalyst preparation process can improve the selectivity and stability of the catalyst in the propylene ammoxidation reaction, but the catalyst evaluation is also carried out under relatively low load conditions.

[0006] The above methods show that although the performance of the catalyst can be improved to a certain extent by controlling the spatial distribution of the elements in the catalyst or adding appropriate carrier modifiers, it still cannot solve the problem of low acrylonitrile yield and poor stability of the current propylene ammoxidation catalyst under high load conditions. Summary of the invention

[0007] In order to overcome the problems of low target product yield and poor stability of catalysts used for ammoxidation reactions in the prior art under high load conditions, the present invention provides a catalyst for preparing acrylonitrile by ammoxidation of propylene, a preparation method and an application thereof. The catalyst of the present invention has high propylene ammoxidation activity and acrylonitrile selectivity in the propylene ammoxidation reaction, and can maintain a high acrylonitrile single-pass yield for a long time under high load conditions.

[0008] A first aspect of the present invention provides a catalyst for preparing acrylonitrile by ammoxidation of propylene, the catalyst comprising an active component and a carrier. When the catalyst is subjected to a programmed temperature reduction experiment, the ratio of the peak intensity of a first reduction peak with a peak temperature between 400 and 600° C. to a second reduction peak with a peak temperature between 600 and 800° C. is 2.5:1 to 1.5:1.

[0009] In the above technical solution, the programmed temperature reduction experimental conditions are conventional conditions in the art. For example, in the above technical solution, the catalyst is subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min.

[0010] In the above technical solution, the peak temperature of the first reduction peak is between 475 and 575° C., and the peak temperature of the second reduction peak is between 650 and 750° C., wherein the peak temperature of the second reduction peak is 100 to 140° C. higher than the peak temperature of the first reduction peak.

[0011] In the above technical solution, the active component is a composite oxide, including oxides of at least three elements: Fe, Mo, and Bi, with the atomic molar ratio of Bi / Mo being 0.005-0.30, preferably 0.01-0.20; and the atomic molar ratio of Fe / Mo being 0.02-1.0, preferably 0.1-0.75.

[0012] In the above technical solution, the active component is a composite oxide, preferably a composite oxide represented by formula (1):

[0013] A a B b C c D d Fe e Bi f Mo g O x (1)

[0014] Among them, A may or may not be contained, and A is selected from at least one of Li, Na, K, Rb and Cs; B may or may not be contained, and B is selected from at least one of Ca, Ba, Sr, Mn, Co, Ni, Zn, Mg, Al, Cr, B and P; C may or may not be contained, and C is selected from at least one of rare earth elements, preferably La, Ce, Pr, Nd, Sm; D may or may not be contained, and D is selected from at least one of Zr, Ti, V, Nb, Sb, Te and W.

[0015] The value range of a is 0 to 3, the value range of b is 0 to 15, the value range of c is 0 to 5, the value range of d is 0 to 6, the value range of e is 0.1 to 12, the value range of f is 0.01 to 5, the value range of g is 9 to 16, and x is the total number of oxygen atoms required to satisfy the valence of each element in the above active components.

[0016] In the above technical scheme, the value range of a is preferably 0.05 to 2.5, including but not limited to: 0.06, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 1.00, 1.50, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.40, 2.50.

[0017] In the above technical scheme, the value range of b is preferably 1 to 12.5, including but not limited to: 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5.

[0018] In the above technical scheme, the value range of c is preferably 0.01 to 3, including but not limited to: 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.50, 2.00, 2.50, 3.00.

[0019] In the above technical solution, the value range of d is preferably 0.1 to 4, including but not limited to: 0.2, 0.6, 1.0, 1.4, 1.8, 2.2, 2.6, 3.0, 3.4, 3.8, 4.0.

[0020] In the above technical solution, the value range of e is preferably 0.5 to 10, including but not limited to: 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0.

[0021] In the above technical solution, the value range of f is preferably 0.01 to 3, including but not limited to: 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1. 60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.00.

[0022] In the above technical solution, the value range of g is preferably 10-15, including but not limited to: 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0.

[0023] In the above technical solution, the composite oxide contains at least one of A, B, C and D, that is, at least one of a, b, c and d is not zero.

[0024] In the above technical solution, the range of f / g is 0.005-0.30, preferably 0.01-0.20; the range of e / g is 0.02-1.0, preferably 0.1-0.75.

[0025] In the above technical solution, the carrier is silicon dioxide.

[0026] In the above technical solution, based on the weight of the catalyst, the content of the active component in terms of oxide is 30% to 80%, and the content of the carrier is 20% to 70%.

[0027] A second aspect of the present invention provides a method for preparing the above-mentioned propylene ammoxidation catalyst for preparing acrylonitrile, comprising the following steps:

[0028] (a) dissolving a Mo precursor and an optional D element precursor to obtain a mixed solution I;

[0029] (b) dissolving an Fe precursor, a Bi precursor, an optional precursor of an element A, an optional precursor of an element B, and an optional precursor of an element C, adding alcohol and a carboxylic acid, and aging to obtain a mixed solution II;

[0030] (c) mixing the mixed solution I obtained in step (a), the mixed solution II obtained in step (b) and the carrier precursor, and adjusting the pH value to obtain slurry I;

[0031] (d) boiling the slurry I obtained in step (c) to obtain slurry I′;

[0032] (e) The slurry I′ obtained in step (d) is spray-dried and calcined to obtain the catalyst.

[0033] In the above technical solution, preferably, the method for preparing the catalyst for preparing acrylonitrile by propylene ammoxidation comprises the following steps:

[0034] (a) dissolving a Mo precursor and a D element precursor to obtain a mixed solution I;

[0035] (b) dissolving an Fe precursor, a Bi precursor, a precursor of an element A, a precursor of an element B, and a precursor of an element C, adding alcohol and a carboxylic acid, and aging to obtain a mixed solution II;

[0036] (c) mixing the mixed solution I obtained in step (a), the mixed solution II obtained in step (b) and the carrier precursor, and adjusting the pH value to obtain slurry I;

[0037] (d) boiling the slurry I obtained in step (c) to obtain slurry I′;

[0038] (e) The slurry I′ obtained in step (d) is spray-dried and calcined to obtain the catalyst.

[0039] In the above technical scheme, in the mixed solution I described in step (a), there is no special requirement for the solvent used. Suitable solvents include any liquid used in the art for convenient mixing of raw materials (such as precursors) when synthesizing catalysts, more specifically including alcohol and water, especially C1-C6 monohydric alcohol and water, more preferably water.

[0040] In the above technical scheme, in the mixed solution II described in step (b), there is no special requirement for the solvent used. Suitable solvents include any liquid used in the art for convenient mixing of raw materials (such as precursors) when synthesizing catalysts, more specifically including alcohol and water, especially C1-C6 monohydric alcohol and water, more preferably water.

[0041] In the above technical solution, in step (b), the alcohol is a polyol, preferably at least one of ethylene glycol, glycerol, 1,2-propylene glycol, 1,3-propylene glycol, sorbitol, and xylitol;

[0042] The carboxylic acid is a polycarboxylic acid, preferably at least one of oxalic acid, citric acid, tartaric acid, and ethylenediaminetetraacetic acid.

[0043] In the above technical solution, the aging conditions described in step (b) include: a temperature of 50 to 80° C. and an aging time of 0.1 to 1 h.

[0044] In the above technical solution, the molar ratio of the total molar number of Fe, Bi and Mo contained in the alcohol, carboxylic acid and active component precursor in the slurry I described in step (c) is (0.01-0.20):(0.01-0.25):1.

[0045] In the above technical solution, in step (c), the pH value is 3 to 6; the pH value is adjusted by a nitric acid solution and / or an ammonia solution. There is no particular limitation on the concentration of the nitric acid solution and / or the ammonia solution, as long as the pH adjustment can be achieved, researchers in the field can select conventionally.

[0046] In the above technical solution, the precursors of the active components Mo, Bi, Fe, A, B, C, and D in the catalyst can be compounds commonly used in the art, and there is no special limitation in the present invention.

[0047] In the above technical solution, in step (c), the carrier precursor is at least one of silica sol, water glass, silica gel and silicate, preferably silica sol. In a specific implementation case, the solid content (in terms of silicon dioxide) of the silica sol is generally 20 to 50 wt%, and the average particle size is 5 to 35 nm. Preferably, the particle size distribution of the silica sol conforms to the normal distribution curve.

[0048] In the above technical solution, in step (d), the conditions for cooking the slurry include: a temperature of 10 to 80° C., a time of 0.1 to 12 h, and a stirring speed of 200 to 800 rpm.

[0049] In the above technical solution, in step (e), the spray drying conditions include: the drying heat source is air, the drying temperature is 250-400°C, the drying time is 0.5-3h, and the average diameter of the spray droplets is 40-200μm.

[0050] In the above technical solution, in step (e), the calcination conditions include: the calcination atmosphere is an oxygen-containing atmosphere (the volume fraction of oxygen is 10% to 50%), the calcination temperature is 200 to 750° C., and the calcination time is 2 to 8 hours.

[0051] A third aspect of the present invention provides a use of the above catalyst in the reaction of ammoxidation of propylene to produce acrylonitrile.

[0052] In the above technical scheme, there is no special limitation on the specifications of propylene, molecular oxygen and ammonia; although the content of low molecular weight saturated hydrocarbons in the raw material propylene has no effect on the reaction, from an economic point of view, the propylene concentration is preferably greater than 85% (mol); fertilizer-grade liquid ammonia can be used as ammonia; the molecular oxygen required for the reaction can be pure oxygen, oxygen-enriched oxygen and air from a technical point of view, but air is preferably used from economic and safety considerations.

[0053] In the above technical scheme, the reaction conditions of the propylene ammoxidation to acrylonitrile reaction include: the molar ratio of propylene: ammonia: air is 1: 1.0-1.5: 8-10.5, preferably 1: 1-1.3: 8.8-10, the reaction temperature is 400-470° C., preferably 410-450° C., the reaction pressure (gauge pressure) is 0.03-0.15 MPa, preferably 0.06-0.14 MPa, and the weight hourly space velocity is 0.045-0.15 h -1 , preferably 0.06~0.12h -1 .

[0054] In the above technical solution, the reaction adopts a fluidized bed process, and the average particle size of the catalyst can be 40 to 60 microns.

[0055] Compared with the prior art, the present invention has the following advantages:

[0056] The lattice oxygen migration ability of the catalyst has a great influence on the activity of the catalyst. A higher lattice oxygen migration ability is conducive to the catalyst completing the reaction in a shorter contact time, that is, improving the catalytic activity of the catalyst under high load conditions. The inventor has found through research that by optimizing the components of the catalyst and adding alcohol and carboxylic acid during the preparation process, the catalytic activity of the catalyst under high load conditions can be improved through optimized preparation conditions. The catalyst of the present invention, in a flowing Ar atmosphere containing 5% H2, is subjected to a temperature-programmed reduction (TPR) experiment at a heating rate of 10°C / min, and contains two reduction peaks, wherein the peak temperature of the first reduction peak is between 400 and 600°C, and the peak temperature of the second reduction peak is between 600 and 800°C, and when the ratio of the peak intensity of the first reduction peak to the second reduction peak is 2.5:1 to 1.5:1, the performance of the catalyst under high load conditions is better.

[0057] The catalyst provided by the present invention is applied to the reaction of preparing acrylonitrile by propylene ammoxidation, and has high propylene ammoxidation activity and acrylonitrile selectivity. At the same time, the catalyst has a long service life under high load conditions, and can maintain a high acrylonitrile per-pass yield for a long time, thereby greatly improving the efficiency and economy of acrylonitrile production. Using the catalyst of the present invention, the propylene conversion rate can reach more than 99%, and the acrylonitrile per-pass yield can reach more than 84%. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1It is the programmed temperature reduction diagram of the catalysts obtained in Example 1, Example 9 and Comparative Example 1. DETAILED DESCRIPTION

[0059] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0060] The present invention will be further described below by way of examples, but these examples do not limit the scope of the present invention in any way.

[0061] In the present invention, the temperature-programmed reduction experiment was carried out using an Autochem II 2920 instrument from Micromeritics. A 50 mg catalyst sample was first heated to 300° C. in a 30 mL / min flowing Ar gas for pretreatment for 1 h, then cooled to room temperature and switched to a flowing Ar atmosphere containing 5% H2, and then heated to 800° C. at a heating rate of 10° C. / min to obtain a temperature-programmed reduction curve of the corresponding catalyst.

[0062] The activity evaluation of the catalyst in the present invention was carried out in a fluidized bed reactor with an inner diameter of 38 mm. The catalyst loading was 400 g, the reaction temperature was 430° C., the molar ratio of the raw materials propylene: ammonia: air was 1: 1.25: 9.7, the reaction pressure (gauge pressure) was 0.085 MPa, and the reaction weight hourly space velocity (WWH) was 0.095 h -1 .

[0063] The conversion rate of propylene, selectivity of acrylonitrile and single-pass yield are used as indicators for evaluating catalyst performance, and their definitions are as follows:

[0064] Propylene conversion (%) = (moles of propylene consumed in the reaction / moles of propylene fed) × 100%;

[0065] Acrylonitrile selectivity (%) = (moles of acrylonitrile produced / moles of propylene consumed in the reaction) × 100%;

[0066] Acrylonitrile single-pass yield (%) = (number of moles of acrylonitrile produced / number of moles of propylene fed) × 100%.

[0067] Example 1 (normal recipe)

[0068] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 17.2 g ethylene glycol and 50.0 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0069] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0070] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0071] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 546°C, the peak temperature of the second reduction peak was 678°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.83:1.

[0072] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.3%, the acrylonitrile selectivity was 84.6%, and the acrylonitrile single-pass yield was 84.0%.

[0073] Example 2 (Bi / Mo, Fe / Mo ratio changes)

[0074] 769.3 g (NH4)6Mo7O 24·4H2O, 74.1 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 194.3 g Bi(NO3)3·5H2O, 465.9 g Ni(NO3)2·6H2O, 93.2 g Co(NO3)2·6H2O, 258.9 g Fe(NO3)3·9H2O, 82.2 g Mg(NO3)2·6H2O, 2.7 g KOH, 76.7 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 16.8 g ethylene glycol and 48.6 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0075] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0076] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 2.0 Bi 1.25 Mo 13.6 O x +50%SiO2

[0077] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 573°C, the peak temperature of the second reduction peak was 687°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.78:1.

[0078] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.7%, the acrylonitrile selectivity was 84.2%, and the acrylonitrile single-pass yield was 83.1%.

[0079] Example 3 (Compared with Example 1, the ratio of the added carboxylic acid types is changed)

[0080] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 17.2 g ethylene glycol and 160.1 g citric acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0081] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0082] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0083] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 536°C, the peak temperature of the second reduction peak was 670°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.93:1.

[0084] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.1%, the acrylonitrile selectivity was 85.3%, and the acrylonitrile single-pass yield was 84.5%.

[0085] Example 4 (Compared with Example 1, the ratio of the types of alcohols added is changed)

[0086] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 31.7 g 1,3-propylene glycol and 50.0 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0087] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0088] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0089] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 565°C, the peak temperature of the second reduction peak was 675°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.85:1.

[0090] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.6%, the acrylonitrile selectivity was 84.7%, and the acrylonitrile single-pass yield was 83.5%.

[0091] Example 5 (Compared with Example 1, the mass of the carrier accounts for 40wt% of the total weight of the catalyst)

[0092] 884.1 g (NH4)6Mo7O 24·4H2O, 85.1 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 267.9 g Bi(NO3)3·5H2O, 535.4 g Ni(NO3)2·6H2O, 107.2 g Co(NO3)2·6H2O, 446.3 g Fe(NO3)3·9H2O, 94.4 g Mg(NO3)2·6H2O, 3.1 g KOH, 88.1 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 20.7 g ethylene glycol and 60.0 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2000 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0093] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0094] 60%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +40%SiO2

[0095] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 545°C, the peak temperature of the second reduction peak was 680°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.86:1.

[0096] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.6%, the acrylonitrile selectivity was 84.7%, and the acrylonitrile single-pass yield was 84.0%.

[0097] Example 6 (Compared with Example 1, Sm replaces Pr, and W replaces Zr)

[0098] 712.9 g (NH4)6Mo7O 24 4H2O, 73.1 g (NH4) 10 W 12 O 41·5H2O was dissolved in 250mL water to obtain a mixed solution I. 216.0g Bi(NO3)3·5H2O, 431.7g Ni(NO3)2·6H2O, 86.4g Co(NO3)2·6H2O, 359.8g Fe(NO3)3·9H2O, 76.1g Mg(NO3)2·6H2O, 2.5g KOH, 72.6g Sm(NO3)3·6H2O were dissolved in 100mL water, and 16.7g ethylene glycol and 48.4g oxalic acid were added thereto, and then aged at 60°C for 0.5h to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g silica sol with a weight concentration of 40wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0099] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0100] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Sm 0.55 W 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0101] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 542°C, the peak temperature of the second reduction peak was 665°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.89:1.

[0102] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.2%, the acrylonitrile selectivity was 84.7%, and the acrylonitrile single-pass yield was 84.0%.

[0103] Example 7 (Compared with Example 1, the contents of Co, Ni, Mg and Zr are different)

[0104] 730.6 g (NH4)6Mo7O 24·4H2O, 52.8g ZrO(NO3)2 were dissolved in 250mL water to obtain mixed solution I. 221.4g Bi(NO3)3·5H2O, 309.7g Ni(NO3)2·6H2O, 265.7g Co(NO3)2·6H2O, 368.8g Fe(NO3)3·9H2O, 117.0g Mg(NO3)2·6H2O, 2.6g KOH, 72.8g Pr(NO3)3·6H2O were dissolved in 100mL water, and 17.1g ethylene glycol and 49.6g oxalic acid were added thereto, and then aged at 60°C for 0.5h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500g silica sol with a weight concentration of 40wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0105] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0106] 50%K 0.15 Co 3.0 Ni 3.5 Mg 1.5 Pr 0.55 Zr 0.75 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0107] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 552°C, the peak temperature of the second reduction peak was 672°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.92:1.

[0108] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.0%, the acrylonitrile selectivity was 85.1%, and the acrylonitrile single-pass yield was 84.2%.

[0109] Example 8 (Compared with Example 6, orthogonal experimental design was used to supplement the implementation of the preferred solution)

[0110] 756.6 g (NH4)6Mo7O 24·4H2O, 72.8g ZrO(NO3)2 were dissolved in 250mL water to obtain mixed solution I. 229.3g Bi(NO3)3·5H2O, 366.5g Ni(NO3)2·6H2O, 45.9g Co(NO3)2·6H2O, 254.6g Fe(NO3)3·9H2O, 121.2g Mg(NO3)2·6H2O, 46.6g RbNO3, 75.4g Pr(NO3)3·6H2O were dissolved in 100mL water, and 49.0g sorbitol and 80.8g tartaric acid were added thereto, and then aged at 70°C for 0.25h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500g silica sol with a weight concentration of 40wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0111] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0112] 50% Rb 1.0 Co 0.5 Ni 4.0 Mg 1.5 Pr 0.55 Zr 1.0 Fe 2.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0113] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 565°C, the peak temperature of the second reduction peak was 670°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.87:1.

[0114] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.2%, the acrylonitrile selectivity was 84.4%, and the acrylonitrile single-pass yield was 83.7%.

[0115] Example 9 (Compared with Example 6, orthogonal experimental design was used to supplement the implementation of the preferred solution)

[0116] 562.5 g (NH4)6Mo7O 24 4H2O, 57.7 g (NH4) 10 W 12 O41 ·5H2O was dissolved in 250mL water to obtain a mixed solution I. 113.6g Bi(NO3)3·5H2O, 238.4g Ni(NO3)2·6H2O, 170.4g Co(NO3)2·6H2O, 378.5g Fe(NO3)3·9H2O, 90.1g Mg(NO3)2·6H2O, 35.5g KOH, 56.0g Pr(NO3)3·6H2O were dissolved in 100mL water, and 20.0g ethylene glycol and 127.2g oxalic acid were added thereto, and then aged at 50°C for 1h to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 3000g silica sol with a weight concentration of 40wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0117] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0118] 40%K 1.5 Co 2.5 Ni 3.5 Mg 1.5 Pr 0.55 W 1.0 Fe 4.0 Bi 1.0 Mo 13.6 O x +60%SiO2

[0119] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 524°C, the peak temperature of the second reduction peak was 653°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.88:1.

[0120] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.7%, the acrylonitrile selectivity was 84.3%, and the acrylonitrile single-pass yield was 83.2%.

[0121] Example 10 (Compared with Example 6, orthogonal experimental design was used to supplement the implementation of the preferred solution)

[0122] 864.5 g (NH4)6Mo7O 24·4H2O, 83.2 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 261.9 g Bi(NO3)3·5H2O, 418.8 g Ni(NO3)2·6H2O, 157.2 g Co(NO3)2·6H2O, 581.8 g Fe(NO3)3·9H2O, 45.2 g Mn(NO3)2·4H2O, 17.5 g CsNO3, 86.1 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 26.1 g 1,2-propylene glycol and 134.2 g citric acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2000 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0123] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0124] 60% Cs 0.25 Co 1.5 Ni 4.0 Mn 0.5 Pr 0.55 Zr 1.0 Fe 4.0 Bi 1.5 Mo 13.6 O x +40%SiO2

[0125] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 538°C, the peak temperature of the second reduction peak was 663°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.89:1.

[0126] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.2%, the acrylonitrile selectivity was 85.0%, and the acrylonitrile single-pass yield was 84.3%.

[0127] Example 11 (Compared with Example 1, the added alcohols and carboxylic acids are not within the appropriate ratio range)

[0128] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 120.4 g ethylene glycol and 250.0 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0129] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0130] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0131] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 564°C, the peak temperature of the second reduction peak was 679°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.45:1.

[0132] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.2%, the acrylonitrile selectivity was 84.0%, and the acrylonitrile single-pass yield was 82.5%.

[0133] Example 12 (changing the pH of the solution to outside the range)

[0134] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 17.2 g ethylene glycol and 50.0 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 7 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0135] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0136] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0137] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 590°C, the peak temperature of the second reduction peak was 753°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.36:1.

[0138] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.3%, the acrylonitrile selectivity was 84.1%, and the acrylonitrile single-pass yield was 82.7%.

[0139] Example 13 (Compared with Example 1, the pulp cooking conditions are not within the required range)

[0140] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 17.2 g ethylene glycol and 50.0 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 130°C and 300 rpm for 4 hours, and the obtained slurry was spray-dried at 325°C for 1 hour with an average diameter of spray droplets of 120 μm to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0141] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0142] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0143] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 556°C, the peak temperature of the second reduction peak was 689°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.43:1.

[0144] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.7%, the acrylonitrile selectivity was 83.7%, and the acrylonitrile single-pass yield was 82.6%.

[0145] Example 14 (Compared with Example 1, spray drying is not within the required range)

[0146] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 17.2 g ethylene glycol and 50.0 g oxalic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 340°C for 1 hour, with an average diameter of the spray droplets of 275 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0147] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0148] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0149] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 553°C, the peak temperature of the second reduction peak was 679°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.46:1.

[0150] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 97.3%, the acrylonitrile selectivity was 83.2%, and the acrylonitrile single-pass yield was 81.0%.

[0151] Comparative Example 1 (without using alcohols and carboxylic acids)

[0152] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain a mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0153] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0154] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0155] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 586°C, the peak temperature of the second reduction peak was 753°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.40:1.

[0156] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 96.5%, the acrylonitrile selectivity was 83.2%, and the acrylonitrile single-pass yield was 80.3%.

[0157] Comparative Example 2 (Changing the Type of Carboxylic Acid or Alcohol)

[0158] 736.7 g (NH4)6Mo7O 24·4H2O, 70.9 g ZrO(NO3)2 were dissolved in 250 mL water to obtain mixed solution I. 233.2 g Bi(NO3)3·5H2O, 446.1 g Ni(NO3)2·6H2O, 89.3 g Co(NO3)2·6H2O, 371.9 g Fe(NO3)3·9H2O, 78.7 g Mg(NO3)2·6H2O, 2.6 g KOH, 73.4 g Pr(NO3)3·6H2O were dissolved in 100 mL water, and 20.6 g n-butanol and 90.7 g trichloroacetic acid were added thereto, and then aged at 60°C for 0.5 h to obtain mixed solution II. Then, mixed solution I, mixed solution II and 2500 g silica sol with a weight concentration of 40 wt% were mixed, and the pH was adjusted to 3 to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and the obtained slurry was spray-dried at 325°C for 1 hour, with an average diameter of the spray droplets of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0159] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0160] 50%K 0.15 Co 1.0 Ni 5.0 Mg 1.0 Pr 0.55 Zr 1.0 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0161] When the catalyst was subjected to a programmed temperature reduction experiment in a flowing Ar atmosphere containing 5% H2 at a heating rate of 10°C / min, the peak temperature of the first reduction peak was 573°C, the peak temperature of the second reduction peak was 732°C, and the peak intensity ratio of the first reduction peak to the second reduction peak was 1.42:1.

[0162] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 97.6%, the acrylonitrile selectivity was 84.6%, and the acrylonitrile single-pass yield was 82.6%.

[0163] Table 1 Catalyst composition and properties of each example

[0164]

[0165]

[0166] Table 1 Catalyst composition and properties of each example (continued)

[0167]

[0168]

[0169] Table 2 Catalyst activity evaluation results for each case

[0170]

[0171]

[0172] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for preparing acrylonitrile by ammoxidation of propylene, characterized in that: The catalyst comprises an active component and a carrier. When the catalyst is subjected to a programmed temperature reduction experiment, the ratio of the peak intensity of a first reduction peak with a peak temperature between 400 and 600° C. to a second reduction peak with a peak temperature between 600 and 800° C. is 2.5:1 to 1.5:

1.

2. The catalyst according to claim 1, characterized in that The peak temperature of the first reduction peak is between 475 and 575° C., and the peak temperature of the second reduction peak is between 650 and 750° C.; and / or, the peak temperature of the second reduction peak is 100 to 140° C. higher than the peak temperature of the first reduction peak.

3. The catalyst according to claim 1, characterized in that The active component is a composite oxide, which at least includes oxides of three elements: Fe, Mo and Bi.

4. The catalyst according to claim 3, characterized in that The composite oxide has the following general formula: a B b C c D d Fe e Bi f Mo g O x , wherein A is selected from at least one of Li, Na, K, Rb and Cs, B is selected from at least one of Ca, Ba, Sr, Mn, Co, Ni, Zn, Mg, Al, Cr, B and P; C is selected from at least one of rare earth elements, and D is selected from at least one of Zr, Ti, V, Nb, Sb, Te and W; and / or, a is in the range of 0 to 3, b is in the range of 0 to 15, c is in the range of 0 to 5, d is in the range of 0 to 6, e is in the range of 0.1 to 12, f is in the range of 0.01 to 5, g is in the range of 9 to 16, and x is the total number of oxygen atoms required to satisfy the valence of each element in the above-mentioned active components.

5. The catalyst according to claim 3, characterized in that In the active components, the atomic molar ratio of Bi / Mo is 0.005-0.30, preferably 0.01-0.20; the atomic molar ratio of Fe / Mo is 0.02-1.0, preferably 0.1-0.

75.

6. The catalyst according to claim 1, characterized in that The carrier is silicon dioxide.

7. The catalyst according to claim 1, characterized in that Based on the weight of the catalyst, the content of active components in the form of oxides is 30% to 80%, and the content of the carrier is 20% to 70%.

8. The method for preparing the catalyst according to any one of claims 1 to 7, comprising the following steps: (a) dissolving a Mo precursor and an optional D element precursor to obtain a mixed solution I; (b) dissolving an Fe precursor, a Bi precursor, an optional precursor of an element A, an optional precursor of an element B, and an optional precursor of an element C, adding alcohol and a carboxylic acid, and aging to obtain a mixed solution II; (c) mixing the mixed solution I obtained in step (a), the mixed solution II obtained in step (b) and the carrier precursor, and adjusting the pH value to obtain slurry I; (d) boiling the slurry I obtained in step (c) to obtain slurry I'; (e) The slurry I' obtained in step (d) is spray-dried and calcined to obtain the catalyst.

9. The method for preparing the catalyst according to claim 8, characterized in that: The aging conditions in step (b) include: a temperature of 50 to 80° C. and an aging time of 0.1 to 1 h; and / or, In step (d), the conditions for cooking the pulp include: a temperature of 10 to 80° C., a time of 0.1 to 3 hours, and a stirring speed of 200 to 1000 rpm; and / or, In step (e), the spray drying conditions include: the drying heat source is air, the drying temperature is 250-400° C., the drying time is 0.5-3 hours, and the average diameter of the spray droplets is 40-200 μm.

10. The method for preparing the catalyst according to claim 8, characterized in that: In step (b), the alcohol is a polyol, preferably at least one of ethylene glycol, glycerol, 1,2-propylene glycol, 1,3-propylene glycol, sorbitol, and xylitol; the carboxylic acid is a polycarboxylic acid, preferably at least one of oxalic acid, citric acid, tartaric acid, and ethylenediaminetetraacetic acid; and / or, in step (c), the carrier precursor is at least one of silica sol, water glass, silica gel, and silicate, preferably silica sol.

11. The method for preparing the catalyst according to claim 8, characterized in that: In step (c), the molar ratio of the total molar number of Fe, Bi and Mo contained in the alcohol, carboxylic acid and active component precursor in the slurry I is (0.01-0.20):(0.01-0.25):

1.

12. The method according to claim 8, characterized in that: In step (c), the pH value is 3-6.

13. The method according to claim 8, characterized in that: In step (e), the calcination conditions include: the calcination atmosphere is an oxygen-containing atmosphere, the calcination temperature is 200-750° C., and the calcination time is 2-8 hours.

14. Use of the catalyst according to any one of claims 1 to 7 in the preparation of acrylonitrile by ammoxidation of propylene.

Citation Information

Patent Citations

  • Catalyst for non-carrier high-activity high-selectivity ammoxidation preparation of 2,6-dichlorobenzonitrile, preparation method and applications thereof

    CN110404528A

  • Ammonia oxidation catalyst as well as preparation method and application thereof

    CN115487820A

  • Fluidized bed catalyst for ammoxidating propylene to prepare acrylonitrile

    CN1310172A

  • Selective Ammonia Oxidation Catalysts

    US20090180943A1

  • Method for producing ammoxidation catalyst and method for producing acrylonitrile

    US20190126262A1